PENDAMPINGAN PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MEDIA TEKNOLOGI PADA GURU DI SMP MADINATUL ILMU MUARA GEMBONG - Rina Febriana; Ivan Hanafi; Rizka Putri Aulia Rahmah; Meilissa Nabila (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Muara Gembong is the most remote coastal area in Bekasi Regency, West Java. This location causes the learning process carried out by teachers to be conventional, both in the use of learning media, methods, and presentation of modules as teaching materials. The purpose of this community service (PkM) is to increase participants' knowledge and skills in designing learning tools using Gemini AI, Canva, and Quizziz applications. The training method used is a training method with lecture, participatory and simulation learning techniques. After the training activities, participants filled out an evaluation questionnaire to assess the implementation of training activities. The results of the PkM achieved were an increase in the aspects of (1) the knowledge of teachers at Madinatul Ilmi Islamic Junior High School in making learning tools increased, indicated by a gain value of 0.32 with a percentage of 55% obtained from the pre-test and post-test results (2) The training activities of mentoring the development of technology-based learning tools for teachers at Madinatul Ilmi Muara Gembong Junior High School have a positive effect as evidenced by the teachers being able to understand how to develop more interesting and creative learning tools. The long-term target is to provide convenience for the development of teaching materials and support the improvement of the quality of education in Muara Gembong District. Keywords: learning tools, technology media, application Abstrak Muara Gembong merupakan wilayah pesisir paling ujung di Kabupaten Bekasi, Jawab Barat. Lokasi ini menyebabkan proses pembelajaran yang dilakukan guru-guru masih konvensional, baik dalam penggunaan media pembelajaran, metode, dan penyajian modul sebagai bahan ajar. Tujuan pengabdian pada masyarakat (PkM) ini adalah peningkatan pengetahuan dan keterampilan peserta dalam mendesain perangkat pembelajaran menggunakan aplikasi Gemini AI, Canva, dan Quizziz. Metode pelatihan yang digunakan adalah metode pelatihan dengan teknik pembelajaran ceramah, partisipatif dan simulasi. Setelah kegiatan pelatihan peserta mengisi kuesioner evaluasi untuk menilai penyelenggaraan kegiatan pelatihan. Hasil PkM yang dicapai adalah peningkatan dalam aspek (1) pengetahuan para guru di SMP Islam Madinatul Ilmi dalam membuat perangkat pembelajaran meningkat, ditunjukkan nilai gain 0,32 dengan persentase 55% yang diperoleh dari hasil pre test dan post test (2) Kegiatan pelatihan pendampingan pengembangan perangkat pembelajaran berbasis media teknologi pada guru di SMP Madinatul Ilmi Muara Gembong berpengaruh positif dibuktikan dengan para guru bisa memahami cara mengembangkan perangkat pembelajaran yang lebih menarik dan kreatif. Target jangka panjang adalah memberikan kemudahan untuk pengembangan bahan ajar dan mendukung peningkatan mutu pendidikan di Kecamatan Muara Gembong. Kata Kunci: perangkat pembelajaran, media teknologi, aplikasi